Cómo se da la selección de una o varias metodologías de gestión de proyectos en los emprendimientos de software de aplicaciones en Colombia (2021)
This paper will investigate the question of how a project management methodology is selected when carrying out a software project that in turn involves entrepreneurship. The objective of the research is to determine how this selection of methodology occurs in software projects in Colombia, and in turn to propose an answer to this question through the formulation of a programmed matrix. In this way, the work will be divided into three fundamental research parts, the first consisting of purely theoretical research. To do this, the concepts required for understanding this study were initially addressed, followed by a bibliographic review that allows us to know the current situation of software project methodologies at a global level. The second fundamental part consists of a series of interviews that made it possible to identify the most important characteristics of software projects, as well as the way in which these characteristics influence the projects in which these 5 interviewees work.